APLIKASI MEDIA TUMBUH DAN PERENDAMAN BUI PADA PERKECAMBAHAN JELUTUNG (Dyera costulata (Miq.) Hook, f) - Ning Wikan Utami; EA Widjaja; Arief Hidayat (BERITA BIOLOGI, 2007)
Jelutung {Dyera costulata) is a potential plant species that has good an economic prospect,_especially for timber and latex production. The aim of this research is to know the effect of seed soaking treatments and growth media variation on seed germination of jelutung. The experiment was carried out in the Treub Laboratory, Research Centre for Biology-LIPI, Bogor, using a Complete Randomized Design with two main factors in three replications. The first factor is growth media i.e. peat + saw dush (1:2), peat + cocopeat (1:2), peat + zeolit (1:1), peat + saw dush (1:1), soil + peat (1:1) and soil (control). The second factor is soaking of seeds in fresh water for 0, 6, 12 or 18 hours prior to sowing. The results showed that there was no interaction effect of growth media and seed soaking treatments. However, both factors had individual significant effects on the germination of jelutung. Therefore it is recommended the best media for germination are peat + cocopeat (1:2), peat + zeolit (1:1), (or) peat +saw dush (1:2). These media had pH between 4 - 4.7. Seed soaking prior to sowing is not required for the germination of jelutung seed. In fact, the longer the time of seed soaked, the lower the germination of the seed. The highest germination percentage was 74%,which was recorded in treatment combination of mixed media peat + zeolit (1:1) without or with soaking of the seed in water for6 hours.